Gut Microbiota Confers Resistance of Albino Oxford Rats to the Induction of Experimental Autoimmune Encephalomyelitis - Stanisavljević, Suzana; Dinić, Miroslav; Jevtić, Bojan; Đedović, Neda; Momčilović, Miljana; Đokić, Jelena; Golić, Nataša; Mostarica Stojković, Marija; Miljković, Đorđe (Frontiers in Immunology, 2018)
Albino Oxford (AO) rats are extremely resistant to induction of experimental autoimmune encephalomyelitis (EAE). EAE is an animal model of multiple sclerosis, a chronic inflammatory disease of the central nervous system (CNS), with established autoimmune pathogenesis. The autoimmune response against the antigens of the CNS is initiated in the peripheral lymphoid tissues after immunization of AO rats with CNS antigens. Subsequently, limited infiltration of the CNS occurs, yet without clinical sequels. It has recently become increasingly appreciated that gut-associated lymphoid tissues (GALT) and gut microbiota play an important role in regulation and propagation of encephalitogenic immune response. Therefore, modulation of AO gut microbiota by antibiotics was performed in this study. The treatment altered composition of gut microbiota in AO rats and led to a reduction in the proportion of regulatory T cells in Peyer’s patches, mesenteric lymph nodes and in lymph nodes draining the site of immunization. Up‐regulation of interferon‐ and interleukin‐17 production was observed in the draining lymph nodes. The treatment led to clinically manifested EAE in AO rats with more numerous infiltrates and higher production of interleukin-17 observed in the CNS. Importantly, transfer of AO gut microbiota into EAE-prone Dark Agouti rats ameliorated the disease. These results clearly imply that gut microbiota is an important factor in AO rat resistance to EAE and that gut microbiota transfer is an efficacious way to treat CNS autoimmunity. These findings also support the idea that gut microbiota modulation has a potential as a future treatment of multiple sclerosis.